Phonetic Alterations Caused by Different Lingual Appliances - Paolo Albertini; Laura Giraud; Francesca Cremonini; Mario Palone (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the differences in phonetic alterations caused by three different lingual appliances, all bonded in sequence on the same patients. Material and Methods: Lingual brackets (STb, Incognito and Harmony) were bonded from 1.3 to 2.3 with a 0.013 CuNiTi archwire. The text was formulated to evaluate the phonetic variations in a controlled context (logatomi) and more casual sentences. The recording of the text was performed at time t0 (before positioning the brackets), t1 (after positioning the brackets) and t2 (60 minutes after positioning the brackets). An ANOVA-type analysis was performed. Results: A significant correlation was confirmed between the effects of all the linguistic methods used compared to the absence of the same. The most influenced acoustic variables were the center of gravity of the acoustic spectrum of the analyzed sounds (CoG) and the number of zero crossings of the instantaneous amplitude curve of the considered signal. Conclusion: The effects deriving from the positioning of the various brackets were relatively contained: in some cases, for some subjects, for some consonants and in specific contexts, some brackets may occasionally be less invasive than others. However, no lingual system was systematically better than others regarding phonetic alterations.